Executive Committee Minutes 2010-08-26 - Academic Senate:::::::::
Resolutions from T. Lease: Support for Director of Diversity and Inclusive Excellence and Director of Undergraduate Studies, Faculty Eligible for Emeritus Status, Approval of Faculty for the Campus Reengineering Committee, Faculty Governance Reassigned Time